Existência de soluções Multi-Bump para uma classe de problemas quasilineares - Santos, Robert Wagner Rocha dos (2019)
Using variational methods we show the existence of a positive Multi-Bump solutions for the following class of quasilinear problems:    −∆pu + (λV (x) + Z(x))u p−1 = f(u), on R N u ∈ W1,p(R N ), (Pλ) where ∆pu = div (|∇u| p−2∇u) is the p-Laplacian operator, 2 ≤ p < N, λ ∈ (0,∞) is a parameter, f : R → R is a continuous function with subcritical growth and V, Z : R N → R are continuous functions which verify some hypotheses.